Teaching Skills For Small Groups and Individuals at Inpres Roong Elementary School - Romi Mesra; Paulus Robert Tuerah; Yenni Melia; Atri Waldi; Leonita Kolang (Departement of Mathematics Education, 2023)
The purpose of this study is to explain the small group and individual learning processes in the Indonesian language topic for grade 3 students at SD Inpres Roong. The descriptive qualitative approach was employed in this investigation. The topic of the study was a third-grade Indonesian language instructor at SD Inpres Roong. Data collecting methods included observation, interviews, and documentation. An observation sheet was employed as the study instrument. The study's findings revealed that teachers used small group and individual teaching approaches effectively. Teachers' use of small group and individual abilities should be more innovative in their teaching and learning implementation. Individuals and should be accustomed to using small group and individual skills with the procedures or steps contained in small group skills, and individuals are of course important in explaining material in class so that students can understand clearly and easily understand because being a student who will later become a teacher must have problems explaining tasks and responsibilities, namely teaching, and thus students must face challenges that will be faced with teaching.